Frataxin deficiency in Friedreich's ataxia is associated with reduced levels of HAX-1, a regulator of cardiomyocyte death and survival. (15th January 2020) - Tiano, Francesca; Amati, Francesca; Cherubini, Fabio; Morini, Elena; Vancheri, Chiara; Maletta, Sara; Fortuni, Silvia; Serio, Dario; Quatrana, Andrea; Luffarelli, Riccardo; Benini, Monica; Alfedi, Giulia; et al.
Abstract: Frataxin deficiency, responsible for Friedreich's ataxia (FRDA), is crucial for cell survival since it critically affects viability of neurons, pancreatic beta cells and cardiomyocytes. In FRDA, the heart is frequently affected with typical manifestation of hypertrophic cardiomyopathy, which can progress to heart failure and cause premature death. A microarray analysis performed on FRDA patient's lymphoblastoid cells stably reconstituted with frataxin, indicated HS-1-associated protein X-1 ( HAX-1 ) as the most significantly upregulated transcript (FC = +2, P < 0.0006). quantitative Reverse Transcription-Polymerase Chain Reaction (qRT-PCR) and western blot analysis performed on (I) HEK293 stably transfected with empty vector compared to wild-type frataxin and (II) lymphoblasts from FRDA patients show that low frataxin mRNA and protein expression correspond to reduced levels of HAX-1. Frataxin overexpression and silencing were also performed in the AC16 human cardiomyocyte cell line. HAX-1 protein levels are indeed regulated through frataxin modulation. Moreover, correlation between frataxin and HAX-1 was further evaluated in peripheral blood mononuclear cells (PBMCs) from FRDA patients and from non-related healthy controls. A regression model for frataxin which included HAX-1, group membership and group * HAX-1 interaction revealed that frataxin and HAX-1 are associated both at mRNA and protein levels. Additionally, a linked expression of FXN, HAX-1 and antioxidant defence proteins MnSOD and Nrf2 was observed both in PBMCs and AC16 cardiomyocytes. Our results suggest that HAX-1 could be considered as a potential biomarker of cardiac disease in FRDA and the evaluation of its expression might provide insights into its pathogenesis as well as improving risk stratification strategies.